Recurrent Attacks of Raised Intracranial Pressure in Case of Tuberculous Arachnoiditis - N. O. Ameli; Ch. M. ( Birm ); F. R. C. S. ( E ). F. I. C. S. (Acta Medica Iranica, 1960)
A ase of recurre'nt raised interacranial pressure is described. At operation posterio-rcfossa arachnoiditis was found. Histological examination suggested a Tuberculous etiology. Four months after the operation she died from an apparently acute tuberculoua meningiti